The Story of the Qur’an: Its History and Place in Muslim Life by Ingrid Mattson (Malden, Massachusetts: Blackwell Publishing, 2008. pages 262.) (American Journal of Islam and Society, 2008)
The resources for instructors dealing with the Qur’an in their courses haveimproved in recent yearswith the completion of Jane DammenMcAuliffe’sEncyclopaedia of the Qur’an (Brill: 2001-06) and Cambridge Companionto the Qur’an (Cambridge University Press: 2006) and Andrew Rippin’sBlackwell Companion to the Qur’an (Balckwell: 2006). But however usefulthe collected articles of these works are, new students of the Qur’anoften respond more enthusiastically to such narrative approaches as thevignettes in Bruce Lawrence’s The Qur’an: A Biography (AtlanticMonthlyPress: 2007). The more integrated narrative approach of Ingrid Mattson’sThe Story of the Qur’an: Its History and Place in Muslim Life provides anew accessible introduction to the Qur’an and its history. Mattson illuminatesthe perspectives of believers and critical historical scholarship bytelling the story of the continuities and ruptures in the reception, transmission,and interpretation of the Qur’an among diverse communities inchanging historical contexts ...